Reliability and Validity of the AOSpine Thoracolumbar Injury Classification System: A Systematic Review. Issue 2 (April 2019) - Abedi, Aidin; Mokkink, Lidwine B.; Zadegan, Shayan Abdollah; Paholpak, Permsak; Tamai, Koji; Wang, Jeffrey C.; Buser, Zorica
Study Design: Systematic review. Objectives: The AOSpine thoracolumbar injury classification system (ATLICS) is a relatively simple yet comprehensive classification of spine injuries introduced in 2013. This systematic review summarizes the evidence on measurement properties of this new classification, particularly the reliability and validity of the main morphologic injury types with and without inclusion of the subtypes. Methods: A literature search was performed using PubMed and Embase in September 2016. A revised version of the COSMIN checklist was used for evaluation of the quality of studies. Two independent reviewers performed all steps of the review. Results: Nine articles were included in the final review, all of which evaluated the reliability of the ATLICS and had a fair methodological quality. The reliability of the modifiers was unknown. Overall, the quality of evidence for reliability of the morphologic and neurologic classification sections was low. However, there was moderate evidence for poor interobserver reliability of the morphologic classification when all subtypes were included, and moderate evidence for good intraobserver reliability with exclusion of subtypes. The reliability of the morphologic classification was independent of the observer's experience and cultural background. Conclusions: ATLICS represents the most current system for evaluation of thoracolumbar injuries. Based on this review, further studies with robust methodological quality are needed to evaluate the measurement properties of ATLICS. Shortcomings of the reliability studies are discussed.